2018
DOI: 10.1186/s12931-018-0728-9
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2 pathway is activated in idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is the most rapidly progressive and fatal fibrotic disorder, with no curative therapies. The signal transducer and activator of transcription 3 (STAT3) protein is activated in lung fibroblasts and alveolar type II cells (ATII), thereby contributing to lung fibrosis in IPF. Although activation of Janus kinase 2 (JAK2) has been implicated in proliferative disorders, its role in IPF is unknown. The aim of this study was to analyze JAK2 activation in IPF, and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 35 publications
7
146
0
1
Order By: Relevance
“…This reduction in SOCS3 was previously shown in other fibrotic conditions [33,40]. Nevertheless, a recent study by Milara et al showed that lungs from patients with IPF expressed higher levels of STAT3 and JAK2, as well as phosphorylated STAT3 [32]. In another article they showed that this was also the case in pulmonary arteries in IPF [29].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This reduction in SOCS3 was previously shown in other fibrotic conditions [33,40]. Nevertheless, a recent study by Milara et al showed that lungs from patients with IPF expressed higher levels of STAT3 and JAK2, as well as phosphorylated STAT3 [32]. In another article they showed that this was also the case in pulmonary arteries in IPF [29].…”
Section: Discussionmentioning
confidence: 58%
“…A recent study by Milara et al showed that IL-6, via STAT3 phosphorylation, induced proliferation and migration of primary human fibroblasts. They also showed that IL-6 is elevated in BAL and in lung tissues of rats following bleomycin treatment [32].…”
Section: Discussionmentioning
confidence: 97%
“…Persistently activated STAT3, independently as well as in conjunction with TGF-b, drives unregulated wound healing, leading to fibrosis through overexpression of ECM components, e.g., COL1A2 (Papaioannou et al, 2018), MMPs (Matsui et al, 2017), and promoting apoptosis resistance of fibroblasts (Moodley et al, 2003;Habiel and Hogaboam, 2014;Xu et al, 2014a;Milara et al, 2018), aberrant EMT (Kasembeli et al, 2018), etc.…”
Section: Stat3 Involvedmentioning
confidence: 99%
“…In rats administered JSI-124, a Jak2 inhibitor that targets STAT3 indirectly, several markers of bleomycin-induced lung fibrosis were reduced [52]. Several other Jak inhibitors, e.g., Cucurbitacin B, Pacritinib and Ruxolitinib, are at various stages of preclinical and clinical development (Table 1).…”
Section: Stat3 and Fibrosismentioning
confidence: 99%